Metafora Konseptual Dalam Cerita Pendek Berbahasa Inggris Di Platform The Short Story: Kajian Semantik Kognitif - Fadhila Afiya; Sutiono Mahdic; R. Agus Suherman Suryadimulyad (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2021)
This research intends to clarify the forms of  metaphors, conceptual meaning, and image scheme  that appear in the five English short stories named The Short Story online platform by applying cognitive semantics. This is a descriptive qualitative research. The whole result of this research is illustrated by words. The theory used in analyzing the metaphors is from Saeed (2009). Besides, the theory for investigating the scheme is from Cruse and Croft (2004). The result of this research is 12 metaphors that have been classified based on their categories. First, five data of conventional metaphors with conceptual meaning such as life choice, darkness, noise, nervousness, and old. Second, four data of  systematic metaphors with conceptual meaning such as fearness,  compulsion, fire, and waving. Third, two data of asymmetric metaphors with conceptual meaning such as preparation and persistence. The last, one data of abstraction metaphor with conceptual meaning that is hard working. Those data have 4 image schemes, such as force (restraint, compulsion, and counterforce), existence (space, process, object), identity (matching), and unity/multiplicity (merging).